A double phosphabetaine formed from 1, 3, 5-triaza-7-phosphaadamantane (PTA) with acetylenedicarboxylic acid and its Ag(CF3SO3)-based coordination polymer. (22nd June 2022) - Szolnoki, Csenge Tamara; Gál, Gyula Tamás; Kováts, Éva; Papp, Gábor; Horváth, Henrietta; Joó, Ferenc; Kathó, Ágnes; Udvardy, Antal
Abstract: The adduct of acetylenedicarboxylic acid and the water-soluble 1, 3, 5-triaza-7-phosphaadamantane (PTA, 1 ) in 1:2 molar ratio, was synthesized both in aqueous solution and under anhydrous conditions in a planetary ball mill (pbm). The resulting double phosphabetaine (2 ) was characterized by 1 H-, 13 C-, and 31 P-NMR spectroscopy, ESI-mass spectroscopy, and elemental analysis, furthermore, its solid-state structure was determined by single crystal X-ray diffraction. SXRD also revealed that in aqueous solution 2 reacted with AgSO3 CF3 to yield a 2 D polymer. Graphical Abstract: UF0001